2018
DOI: 10.1029/2018gc007703
|View full text |Cite
|
Sign up to set email alerts
|

Watching Dehydration: Seismic Indication for Transient Fluid Pathways in the Oceanic Mantle of the Subducting Nazca Slab

Abstract: Intermediate depth seismicity in subduction zones often occurs in the form of two slab‐parallel bands. We estimated the seismic P to S wave velocity ratio within the shallowest part of the lower seismicity zone (LSZ) in the mantle of the subducting slab of the Central Andean subduction system at 50‐km depth, 30 km below the Moho, using local earthquake data. We find an exceptionally high VP/VS value larger than ∼2.0 that cannot be explained by a realistic solid lithology but requires the presence of fluid‐fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 94 publications
6
61
1
Order By: Relevance
“…Neither in Japan nor Chile do we find anomalous sP to pP differential times for events in the lower layers of the double seismic zones, which argues against deep penetration of water into the upper mantle and, thus, dehydration embrittlement as the mechanism for the lower of the double seismic zone. This is somewhat inconsistent with Bloch et al (2018), who observed very high Vp/Vs in the lower layer. But the depth where they found anomalous Vp/Vs (about 55 km) is shallower than what we observed with sP to pP differential time.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…Neither in Japan nor Chile do we find anomalous sP to pP differential times for events in the lower layers of the double seismic zones, which argues against deep penetration of water into the upper mantle and, thus, dehydration embrittlement as the mechanism for the lower of the double seismic zone. This is somewhat inconsistent with Bloch et al (2018), who observed very high Vp/Vs in the lower layer. But the depth where they found anomalous Vp/Vs (about 55 km) is shallower than what we observed with sP to pP differential time.…”
Section: Discussioncontrasting
confidence: 91%
“…But the depth where they found anomalous Vp/Vs (about 55 km) is shallower than what we observed with sP to pP differential time. Using a similar approach to Lin and Shearer (2007) and Bloch et al (2018), we do not find high Vp/Vs in the lower layer in the Japan subduction zone ( Figure S7). It could be interesting to explore deeper regions in the lower layer of the double seismic zone in northern Chile using the approach of Bloch et al (2018) to see if both measurements are consistent with each other and confirm if dehydration extends deeper in the lower layer in warm slabs.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Another important characteristic used to study rocks at depth is the V P / V S ratio, which is of specific interest in receiver function imaging, because this method is based on the differences in arrival times of converted waves at boundaries with contrasting seismic velocities (Kind et al, ). Additionally, the V P / V S ratio is often used to extract lithological information of the rocks at depth or to detect the presence of fluids (e.g., Bloch et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%